Studies on Prionoceridae (Coleoptera: Cleroidea). II. A revision of the genus Prionocerus Perty, 1831 - Geiser, Michael (Zootaxa, 2010)
The genus Prionocerus Perty, 1831 is revised. Eight species are recognised: P. coeruleipennis Perty, 1831 (= P. coeruleipennis var. diversicollis Pic, 1920, n. syn.); P. bicolor Redtenbacher, 1868 (= P. pertii Castelnau, 1836, n. syn.); P. opacipennis (Pic, 1920) (transferred from Idgia Castelnau, 1836); P. viridiflavus Geiser, 2007 and four new species: P. paiensis n. sp. (Thailand); P. malaysiacus n. sp. (Malaysia); P. championi n. sp. (Indonesia) and P. wittmeri n. sp. (Indonesia). All previous synonymies of taxa under P. coeruleipennis and P. bicolor could be confirmed through study of the relevant types. Prionocerus pertii Castelnau, 1836 was found to be conspecific with P. bicolor Redtenbacher, 1868, but this senior synonymy was submitted to the ICZN proposing it as nomen oblitum. Prionocerus thibetanus Obenberger, 1918 is newly synonymised with Idgia viridescens Gorham, 1895. Prionocerus huegeli Redtenbacher, 1868 and P. hirtus Walker, 1871 are confirmed to belong to Idgia, the latter has to be treated as a nomen dubium. The infrageneric phylogeny of Prionocerus, its relationships to other Prionoceridae, as well as its life history, ecology and biogeography are discussed.